Experimental and finite element evaluation of bending for aluminium - Muhammad Hafiz, Azam (2012)
This thesis studies the effect of anisotropy to the deformation of springback in sheet metal forming and reliability of finite element method in sheet metal bending of Aluminium 1100 with the thickness 1 mm. This thesis focuses on tensile test experiment, bending experiment and finite element experiment. Tensile test experiment was done to determine the material properties of aluminium to put in the finite element simulation. The bending process was done using U-die to define the angle of springback in aluminium. The finite element simulation was done by using ABAQUS 6.7 to determine the angle of springback. The results of the experiments were analysed in order to determine the reliability of finite Element. The results show springback increased when the angle of rolling direction is higher. The lowest angle of springback was occurs at the 0° of rolling direction. Based on project, it was concluded that the parameters of anisotropy affect springback angle. It was found the 0° provides a suitable condition in U-die bending process. The finding from this project is the finite element method might be use in order to predict the springback angle of die designing.